A systematic review and meta-analysis of acupuncture for improving learning and memory ability in animals. Issue 1 (December 2016) - Huang, Kai-Yu; Liang, Shuang; Yu, Mei-Ling; Fu, Shu-Ping; Chen, Xia; Lu, Sheng-Feng
Abstract Background Memory loss is the most prominent symptoms of brain aging, but there is currently no evidence-based treatment strategy. Acupuncture has been widely used in China and the effectiveness for improving learning and memory has been mentioned in previous studies. We conducted this systematic review and meta-analysis to evaluate the effectiveness of acupuncture for improving learning and memory in animal experiments. Methods We searched Pubmed, Embase, Ovid Medline(R), the China National Knowledge Infrastructure (CNKI), Chinese Science and Technology Periodical Database (VIP) and Wanfang data Information Site to collect studies published up to December 2015. Study quality for each included article was evaluated according to the CAMARADES 10-item checklist. Outcome measure is Morris water maze. A meta-analysis was conducted according to the Cochrane systematic review method by using RevMan 5.3 software. Results Forty-two studies involving 944 animals were included. The quality score of the studies ranged from 2 to 8, with a mean of 5.3. Meta-analysis results showed that 24 studies reported significant effect of acupuncture for decreasing escape latency (−3.00, 95 % CI: −3.78 −2.23, P < 0.00001), 14 studies reported significant effect of acupuncture for increasing frequency of cross platform (2.57, 95 % CI: 1.92 3.22, P < 0.00001), and 7 studies reported significant effect of acupuncture for increasing time in target quadrant (2.00, 95 % CI: 1.10 2.91, P < 0.00001) compared with the control group. Conclusions These findings show acupuncture has a potential role in improving learning and memory ability in animal models, suggesting it as a candidate therapy for memory loss of aged brain.